Who takes care of the rural elderly? analysis of family arrangement for old-age security in rural China - Yang, Shengwan (The Hague, Netherlands Institute of Social Studies, 2000)
Based mainly on three national surveys, investigates support systems for the rural elderly in China. Highlights the role of the family in providing care and financial assistance, outlines the formal support system and makes policy recommendations.
"Feburary 2000"
Includes bibliographic references.
PI-8200 donated by Department of Global Development Cornell University Ithaca.
Keywords: Older people -- China -- Social conditions; Older people -- Family relationships -- China; Aging -- China; Older people -- China -- Economic conditions